Analysis of the Influence of Good Governance and Leadership on the Performance of the Bombana Regency Regional Government - Agustina, Ria; Tenriwaru, Tenriwaru; Tjan, Juliyanty Sidik (Invoice : Jurnal Ilmu Akuntansi, 2024)
This research aims to test the analysis of the influence of good governance and leadership on the performance of the Bombana regional government. The data in this research were obtained from heads of SKPD (Regional Apparatus Work Units) or OPD (Regional Apparatus Organizations) who are in charge of public services, both involved in regional financial and non-financial management in the Bombana Regency Government who were willing to be respondents. This research uses primary data by conducting direct research in the field by giving questionnaires/statement sheets to respondents and sampling using the census method with a total of 30 department heads from several SKPD or OPD in Bombana Regency as respondents. Data analysis techniques were carried out using descriptive statistical analysis and SPSS 26.0. The research results show that good governance has a positive and significant effect on government performance. The better the good governance, the better the level of government performance. good governance can stimulate public participation in monitoring and evaluating government policies. By providing more detailed financial information, the public can be more actively involved in the decision-making process. Leadership has a positive and significant effect on government performance, the better the leadership, the better the level of government performance. This is where the central role of leaders acts as being able to strengthen the capacity and skills of government officials regarding accounting, improving the quality of financial management at all levels of government.